Factors influencing islamic banking students' career paths in UiTM Segamat, Johor / Engku Nur Alia Syahirah Engku Mohd Adlin - Engku Mohd Adlin, Engku Nur Alia Syahirah (2018)
This paper is conducted to study the factors influencing Islamic banking students' career paths in UiTM Segamat, Johor. The population of this study is UiTM Segamat, Johor students and sample of study (respondent) is Islamic banking students. Sampling technique is convenience sampling and using primary data that is using questionnaire is used to collect the data. Statistical Package for Social Science (SPSS) 22 software used to analyse the data and method for data analyse using Frequency Analysis, Descriptive Analysis, Multiple Linear Regression, Correlation Analysis and Reliability Analysis (Cronbach's Alpha). The questionnaire will be distributed to 100 Islamic banking students in UiTM Segamat, Johor. The researcher have also conducted pilot test for preliminary test on these dimensions. This questionnaire will focus on dependent variable which is career path while the independent variables are intrinsic motivation, extrinsic motivation, influence of third parties and career exposure. The researcher of the study expects to know whether intrinsic motivation, extrinsic motivation, influence of third parties, career exposure as independent variables are significant with the dependent variable, career path.